The Effect of Vocal Warm up and Cool Down Exercises on the Acoustic Characteristics in Speech and Language Pathologists: A Pilot Study - Fariba Iranpour; Leila Ghelichi (Function and Disability Journal, 2023)
Background and Objectives: This cross-sectional study aims to explore the effect of vocal warm-up and cool-down exercises (VWCE) on the acoustic characteristics of speech and language pathologists (SLPs). Methods: This pilot study was conducted on 18 SLPs. The participants received VWCE for 6 weeks, 3 times per week, every other day. The acoustic characteristics, including jitter, shimmer, and harmonic to noise rat (HNR) were outcome measures. All outcome variables were measured before the exercise program (T0), after the end of the 9th session (T1), and after the end of the 18th session (T2). Results: A significant decrease was observed in jitter after the VWCE at T1 and T2. The shimmer showed significant decreases in T2 compared to T0 (P<0.05). No significant difference was observed in shimmer in T1 compared to T0 and T2. The HNR indicated a significant increase at T2 compared to T0 and T1 (P<0.05). No significant difference was observed in HNR in T1 compared to T0. Conclusion: This pilot study demonstrated that vocal warm-up and cool-down exercises significantly improved the acoustic characteristics in SLPs.